Injury-related treatments and outcomes in preschool children with autism spectrum disorder: Study to Explore Early Development (SEED). (October 2019) - DiGuiseppi, Carolyn; Sabourin, Katherine R.; Levy, Susan E.; Soke, Gnakub N.; Lee, Li-Ching; Wiggins, Lisa; Schieve, Laura A.
Highlights: Parent-reported treatments and outcomes of medically-attended injurieswere compared in children with ASD versus control children. Compared to children with other developmental delays or disorders, children with ASD were less likely to receive medication or an injection. Surgical treatment (e.g., for open wounds or fractures) was reported more often for children with ASD than children from the general population. The study groups did not differ in rates of emergency care or hospitalization. Loss of consciousness and long-term or significant behavior change after injury were uncommon and did not differ between study groups. Abstract: Background: Evidence about injury management and outcomes in children with autism spectrum disorder (ASD) is limited. Method: Cross-sectional analyses included children aged 30–68 months with at least one medically attended injury. Standardized diagnostic instruments determined ASD cases. Parent-reported injury treatments and outcomes were examined in ASD cases (n = 224) versus developmental delays/disorders (DD) (n = 188) and population (POP) (n = 267) controls, adjusting for child and family characteristics using logistic regression. Results: Injury characteristics were similar between groups. Most children (82.5%) had emergency care (EC) or hospitalization after injury. Nearly half (46.4%) ever received a medication or injection, mostly analgesics (53.4%) and local anesthetics (23.8%), while 9.4% ever received surgery, most often for open wound (47.0%) or fracture (16.7%). ASD group children were less likely than DD group children to receive medication/injection (41.1% vs. 53.2%, adjusted odds ratio [aOR] = 0.60 [0.40, 0.90]); receipt of EC/hospitalization and surgery were comparable. Children with ASD more often had surgery than POP children (14.3% vs. 4.9%, aOR = 2.62 [1.31, 5.25]); receipt of EC/hospitalization and medication/injection were similar. Loss of consciousness was uncommon (ASD = 6.3%, DD = 5.3%, POP = 3.4%), as was long-term or significant behavior change (ASD = 5.4%, DD = 3.2%, POP = 3.2%); differences were not significant. Conclusions: Injured children with ASD received fewer medications/injections than children with non-ASD developmental delays/disorders and more surgical treatments than general population children. Injury management was otherwise similar between groups. Understanding whether these results reflect child or injury characteristics or provider perceptions about behaviors and pain thresholds of children with ASD, and how these may influence care, requires further study.